Neratinib a MST 1 inhibitor coated with Chitosan-alginate nanocarrier as a promising oral drug to inhibit pancreas cell apoptosis, stimulate insulin secretion, and restore Glycemia in type 1 Diabetes Mellitus - Nabila Anisa Harum; Zumara Ma'rifah Azzahra; Faizah Sugiarto; Arifa Mustika (Konsorsium Ilmu Biomedik Indonesia (KIBI), 2021)
Type 1 Diabetes Mellitus (T1DM) is a polygenic disorder in which autoimmunity destroys pancreatic beta cells, culminating in an absolute insulin secretion deficiency. Neratinib is an MST1 inhibitor to improve β-cell survival cells coated with alginate calcium nanocarrier encapsulated with chitosan that allows the retention of the packaged oral drug until it reaches specific target cells. This review aims to determine the potential of Neratinib as a Mammalian sterile 20-like kinase 1 Inhibitor, which is carried by nanocarrier chitosan-alginate as an alternative cutting edge oral drug for T1DM by preventing the apoptosis of beta cells.. Neratinib coated with chitosan-alginate nanocarrier and packaged in the form of an oral drug can be used as an advanced T1DM therapy. Future perspective needs further experimental and clinical trials to obtain concrete scientific evidence.